Strategy For Development of Cold Chain Facilities and Public Fuel Filling Stations for Fishermen in Ternate Archipelago Fishery Port - Kamarudin, Kamarudin; Karman, Amirul; Najamuddin, Najamuddin; Taeran, Imran; Achmad, M. Djanib; Muksin, Darmiyati (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Fulfilling the need for ice blocks and fuel oil (BBM) for going to sea is also experiencing problems. The port has not been able to meet the demand for ice blocks and fuel, so fishermen still have to buy it from outside the port. In order to optimally serve the needs of users at PPN Ternate, a scientific study is needed regarding strategies for developing cold chain facilities and fishermen's public fuel filling stations (SPBUN) PPN Ternate. This research aims to develop a strategy for developing cold chain facilities (ice factory, ABF, and cold storage) and SPBUN at the Ternate archipelago fishing port. The research was carried out at PPN Ternate, North Maluku Province, from May - June 2023. Field data was collected for 2 weeks, namely 15-29 May 2023. This research used the case method. The results of the research show that the level of utilization of the ice factory (100.72%), cold storage (112.74%), and SPBUN (diesel 101.53%) has exceeded the optimal limit, while for pertalite and kerosene it requires distribution from Pertamina (pertalite 8 .50 KL/month, and kerosene 13.17 KL/month), while the air blast freezer (ABF) is not optimal (71.31%). The strategy for developing cold chain facilities and public fuel filling stations for fishermen at PPN Ternate includes: (1) Improving the quality of service at PPN Ternate; (2) Increasing cooperation indeveloping cold chain facilities and SPBUN at PPN Ternate; (3) Development of an integrated cold chain; and (4) Improvement of public fuel filling station (SPBUN) facilities for fishermen